Tinjauan Kuat Tekan Dan Kuat Lentur Dinding Panel Dengan Menggunakan Perkuatan Diagonal Tulangan Baja - Hartadi, Setia (2016)
ABSTRACTION Along with the rapid development of the current development , the use of brick as a building wall can be replaced with a wall panel usage . Wall panel is one of the technological developments in the field of precast concrete ( precast) . Precast wall ( precast) is not a structural element , which has sought to use a relatively light weight so it does not place an increased burden for the structure of the building . In this study aims to determine how much the compressive strength and flexural strength reinforcement diagonal wall panels without steel reinforcement and wall panels with a diagonal reinforcement steel reinforcement. Reinforcing steel is a material that has a high tensile strength. In this study attempted reinforcing steel reinforcement is applied as a diagonal with water factor cement (fas) of 0.45. the sample used is a concrete cylinder with a height of 15 cm and a diameter of 30 cm sebanyk 5 pieces, wall panels with a length of 100 cm, width of 50 cm and a height of 7 cm 16 units. From the results of research conducted at the Laboratory of Building Materials, Department of Civil Engineering, Faculty of Engineering, Universitas Muhammadiyah Surakarta, obtained an average density of concrete cylinders of 1,709 gr / cm3, so it can be classified as lightweight concrete, with an average compressive strength of 5.83 MPa, whereas the compressive strength testing panel wall without diagonal reinforcement steel reinforcement of 2,094 MPa, while the average value of the compressive strength of a wall panel with a diagonal reinforcement of 2,472 MPa steel reinforcement, of the research results using the value of the diagonal reinforcement steel the higher the compressive strength. In the flexural strength testing panel wall without diagonal reinforcement steel reinforcement amounting to 2.755 MPa, while the average value of flexural strength reinforcement wall panel with a diagonal of 7.214 MPa steel reinforcement, of the results of these studiesby using steel reinforcement diagonal then the higher the compressive strength. Keywords : Wall Panels , Compressive Strength , Strong Flexible, Diagonal Reinforcement Steel Reinforcement